A modified epoxy resin composition suitable for outer coating of steel strand of flexible photovoltaic support and steel strand

Through the modified epoxy resin composition coating technology, the corrosion resistance and temperature resistance of flexible photovoltaic support steel strands in harsh environments is solved, and efficient alternating performance and corrosion resistance are achieved.

CN118703096BActive Publication Date: 2025-03-11BEIJING ACAD OF BUILDING ENG +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410969423.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-19
Publication Date
2025-03-11
Estimated Expiration
2044-07-19

AI Technical Summary

Technical Problem

The existing flexible photovoltaic bracket steel strands are difficult to meet good corrosion resistance and temperature resistance in harsh environments, especially in alternating environments with high and low temperatures.

Method used

The modified epoxy resin composition is used as the coating, including polyurea modified epoxy resin, epoxy group-containing nanotitanium alloy polymer, epoxy modified filler and low molecular weight polyamide with amino-terminated pyridine-containing fluorinated polyamic acid, to form a dense three-dimensional network structure by coating and heating curing.

Benefits of technology

The corrosion resistance and temperature resistance of steel strands are significantly improved, and the retention rate of alternating tensile shear strength of high and low temperatures reaches more than 95%, meeting the temperature and corrosion resistance requirements of flexible photovoltaic brackets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004952710690000031
    Figure BDA0004952710690000031
  • Figure BDA0004952710690000081
    Figure BDA0004952710690000081
  • Figure BDA0004952710690000091
    Figure BDA0004952710690000091
Patent Text Reader

Abstract

The present invention relates to a modified epoxy resin composition and a steel strand suitable for being used as an outer coating of a steel strand body of a flexible photovoltaic support. The composition comprises a component A and a component B, wherein the component A comprises a polyurea-modified epoxy resin, an epoxy-containing nano-titanium alloy polymer, an epoxy-modified filler, and a dispersant; the component B is a compound of a low molecular weight polyamide and an amino-terminated pyridine-containing fluorinated polyamic acid; the number average molecular weight of the amino-terminated pyridine-containing fluorinated polyamic acid is 1000-3000. The steel strand is heat-resistant and corrosion-resistant, and comprises a steel strand body and a coating coated on the outside of the steel strand body, wherein the coating is formed by mixing the component A and the component B in a mass ratio of 1:0.4-0.6, coating the steel strand body, and then curing by heating. The coating prepared by the present invention has excellent high and low temperature alternating resistance and corrosion resistance, and its high and low temperature alternating tensile shear strength retention rate is above 95%; the steel strand coated with the coating is suitable for a flexible photovoltaic support.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer compositions and applications thereof in prestressed steel strands, and in particular relates to a modified epoxy resin composition suitable for being used as an outer coating of a steel strand body of a flexible photovoltaic support and the steel strand. Background Art

[0002] Flexible photovoltaic brackets are equipment designed and installed to support, fix and rotate photovoltaic modules in photovoltaic power generation systems, and are an indispensable part of photovoltaic power generation systems. Photovoltaic flexible brackets are large-span photovoltaic module support structures formed by prestressed flexible cable structures with both ends fixed. Compared with traditional steel frame structures, flexible photovoltaic brackets can save 35% of steel. However, since photovoltaic brackets are mostly set up in harsh environments such as rivers and canyons, the steel strands of the inclined cables, which are subjected to continuous loads, are exposed to humidity, acid rain, solar radiation or high salt spray content for a long time, and are subject to strong high and low temperature changes such as hot summer and cold winter. Therefore, strict and efficient corrosion and temperature protection are required for the steel strands. Steel pipes, grease and galvanizing are usually used to isolate the steel strands from air, prevent corrosion and rust, but the treatment of steel pipes and grease increases the amount of steel and greatly increases the load-bearing capacity of the flexible bracket; the use of galvanized steel strands also has the problem of too short a shelf life.

[0003] The applicant's previous patent CN114057945B disclosed a double-sheathed steel strand cable suitable for photovoltaic flexible support and its preparation method, the double-sheathed steel strand cable includes a prestressed steel strand, the prestressed steel strand is wrapped with an inner sheath and an outer sheath in sequence, the space between the prestressed steel strand and the inner sheath is filled with anti-corrosion lubricating oil, the raw materials of the outer sheath include the following raw materials: high-density polyethylene (HDPE), ultra-high molecular weight polyethylene (UHMWPE), grafted monomer, initiator, toughening agent, lubricant, organic solvent, the grafted monomer is a composition of unsaturated acid and unsaturated naphthyl ether; the inner sheath includes the following raw materials: high-density polyethylene (HDPE), glycidyl methacrylate, initiator, lubricant. The present invention uses high-density polyethylene grafted with unsaturated acid and unsaturated naphthyl ether monomers as the main resin to make the outer sheath of the double-sheathed steel strand cable, and obtains a photovoltaic flexible support cable with good corrosion resistance and ultraviolet performance; but the temperature resistance of the steel strand cable prepared in the patent needs to be further improved.

[0004] Therefore, it is necessary to develop a steel strand suitable for photovoltaic brackets, which should have good corrosion resistance and long-lasting temperature resistance, especially excellent high and low temperature alternating performance. Summary of the invention

[0005] In view of the above-mentioned problems of the prior art, the present invention first provides a modified epoxy resin composition suitable for being used as a coating on the outer surface of a steel strand of a flexible photovoltaic bracket, and at the same time provides a steel strand which is heat-resistant and corrosion-resistant, and comprises a steel strand body and a coating wrapped around the steel strand body, wherein the coating is formed by coating the aforementioned modified epoxy resin composition on the steel strand body and then curing it by heating.

[0006] The technical solution of the present invention is as follows:

[0007] A modified epoxy resin composition suitable for being used as an outer coating for a steel strand of a flexible photovoltaic support, the composition comprising a component A and a component B, wherein the component A comprises a polyurea-modified epoxy resin, an epoxy-containing nano-titanium alloy polymer, an epoxy-modified filler, and a dispersant; the component B is a compound of a low molecular weight polyamide and an amino-terminated pyridine-containing fluorinated polyamic acid; the number average molecular weight of the amino-terminated pyridine-containing fluorinated polyamic acid is 1000 to 3000.

[0008] Furthermore, the amino-terminated pyridine-containing fluorinated polyamic acid is prepared by reacting raw materials including a fluorinated diamine containing pyridine and a dibasic acid anhydride, and the molar ratio of the fluorinated diamine containing pyridine to the dibasic acid anhydride is (1.1-1.3):1.

[0009] Furthermore, the pyridine-containing fluorinated diamine is selected from at least one of 2,3-diamino-5-fluoropyridine, 2,6-diamino-3-fluoropyridine, and 2,6-diamino-3,5-difluoropyridine; and the dibasic acid anhydride is selected from at least one of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) and pyromellitic dianhydride (PMDA).

[0010] Furthermore, the B component is a compound of low molecular weight polyamide and amino-terminated pyridine-containing fluorinated polyamic acid in a mass ratio of 1:(1-3), preferably 1:(2-3).

[0011] Furthermore, the molecular weight of the low molecular weight polyamide in the B component is 600-2000, for example, 200 low molecular weight polyamide, 203 low molecular weight polyamide, 3051 low molecular weight polyamide, 315 low molecular weight polyamide, 650 low molecular weight polyamide, 651 low molecular weight polyamide.

[0012] Furthermore, the amino-terminated pyridine-containing fluorinated polyamic acid in the B component is prepared by the following steps:

[0013] (P1) Under nitrogen protection, a fluorinated diamine containing pyridine is dissolved in an organic solvent, and then a dibasic acid anhydride is added in 2 to 4 batches according to a stoichiometric ratio, and the mixture is reacted at 5 to 10° C. for 3 to 6 hours to obtain an amino-terminated fluorinated polyamic acid solution containing pyridine;

[0014] (P2) After the reaction is completed, the amino-terminated pyridine-containing fluorinated polyamic acid solution is vacuum dried at 40-60° C. for 12-36 hours to obtain the amino-terminated pyridine-containing fluorinated polyamic acid.

[0015] Furthermore, the organic solvent is at least one of dimethylacetamide (DMAC), N,N′-dimethylformamide (DMF), and N-methylpyrrolidone (NMP).

[0016] Furthermore, the A component includes the following raw materials in parts by weight:

[0017]

[0018] The epoxy resin is at least one of bisphenol A epoxy resins with an epoxy value of 0.1 to 0.3 eq / 100g, and the solid content of the epoxy resin solution is 50% to 70%. The raw materials of the polyurea modified epoxy resin include 4,4'-diaminodiphenyl ether, toluene-2,4-diisocyanate and epoxy resin solution.

[0019] Furthermore, the epoxy-containing nano-titanium alloy polymer in the A component is a polycondensate of a bisphenol A-type cyclic resin with an epoxy value of 0.6 to 1.0 eq / 100 g and titanium hydride powder, and the polymerization degree n is 5 to 20.

[0020] Furthermore, the epoxy-modified filler in component A is a filler modified by an epoxy silane coupling agent, the filler is at least one of silicon dioxide, calcium carbonate, and wollastonite, and the median particle size D50 is 10 to 50 μm; the epoxy silane coupling agent is selected from at least one of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 3-(2,3-epoxypropoxy)propyltriethoxysilane, 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane, 3-(2,3-epoxypropoxy)propylmethyldimethoxysilane, 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane, and 2-(3,4-epoxycyclohexane)ethyltriethoxysilane.

[0021] Furthermore, the epoxy modified filler is prepared by a preparation method comprising the following steps:

[0022] (L1) Dry the filler in a drying oven at 80-100° C. for 12-24 hours;

[0023] (L2) putting the dried filler into a high-speed mixer and stirring at 700-900 r / min for 2-5 hours;

[0024] (L3) Spraying a 5-10 wt% epoxy silane coupling agent solution onto the filler surface, increasing the stirring speed to 1200-1500 r / min, stirring for 60-90 min and then stopping the stirring to obtain the epoxy modified filler.

[0025] Preferably, the solvent of the epoxy silane coupling agent solution is ethanol; the amount of the epoxy silane coupling agent used is 1 to 3 wt % of the filler.

[0026] Furthermore, the dispersant in the component A is at least one of BYK-170 and BYK-190.

[0027] In a second aspect, the present invention also provides a flexible photovoltaic support steel strand, comprising a steel strand body and a coating wrapped around the steel strand body, wherein the coating is formed by coating the aforementioned epoxy resin composition on the steel strand body and then curing it by heating, wherein the coating is performed by mixing component A and component B in a mass ratio of 1:0.4 to 0.6.

[0028] The present invention provides a method for preparing the steel strand, comprising the following steps:

[0029] (I) Preparation of component A:

[0030] S1: dissolving 4,4'-diaminodiphenyl ether (ODA) in an organic solvent, then adding toluene-2,4-diisocyanate (TDI), heating under nitrogen protection, and reacting until the reaction is complete. The product is vacuum dried to obtain a polyurea prepolymer;

[0031] S2: putting the polyurea prepolymer obtained in step S1 into a reaction kettle, adding the epoxy resin solution under stirring, heating and reacting; cooling to room temperature to form a polyurea-modified epoxy resin;

[0032] S3: adding epoxy-modified filler, epoxy-containing nano-titanium alloy polymer and dispersant to polyurea-modified epoxy resin, and ball milling in a ball mill for 6 to 12 hours. After the ball milling is completed, a mixed slurry is obtained, which is component A;

[0033] (II) Preparation of component B: low molecular weight polyamide and amino-terminated pyridine-containing fluorinated polyamic acid are mixed and stirred according to a mass ratio to obtain a mixed slurry, namely component B;

[0034] (III) coating: after mixing the component A obtained in step (I) with the component B obtained in step (II) at a mass ratio of 1:0.4-0.6, the mixture is applied to the steel strand, and the coating thickness is controlled at 1.5-2.5 mm; the temperature of the tail section of the coating device is 70-85° C.;

[0035] (IV) Curing: The steel strand coated with the film is heated and cured.

[0036] Furthermore, in step S1, the organic solvent is at least one of dimethylacetamide (DMAC), N,N′-dimethylformamide (DMF), and N-methylpyrrolidone (NMP); the temperature rising reaction is heating to 70-90° C. for 2-4 hours; and the vacuum drying is vacuum drying at 50-80° C. for 12-36 hours.

[0037] Furthermore, in step S2, the temperature-raising reaction is to raise the temperature to 70-80° C. for 3-5 hours.

[0038] Furthermore, in step III, the painting is performed by a coating device with a spring-controlled arm on a roller brush. During painting, the steel strand body passes through the device, driving the roller brush to rotate along the steel strand body.

[0039] Furthermore, in step IV, the heating and curing is performed at 80 to 90° C. for 24 to 48 hours.

[0040] The mechanism of the present invention is described as follows:

[0041] Bisphenol A epoxy resin has excellent bonding properties, but its application is limited due to its poor temperature resistance, poor corrosion resistance and inherent brittleness. The present invention adopts a compound of low molecular weight polyamide and amino-terminated pyridine-containing fluorinated polyamic acid as the B component curing agent to give the coating better high and low temperature alternating resistance and corrosion resistance. The possible reason is that the introduction of pyridine heterocycles and fluorine atoms in pyridine-containing fluorinated polyamic acid brings about the improvement of temperature resistance and corrosion resistance; at the same time, there are a large number of carboxyl groups, amino groups, and amide groups in pyridine-containing fluorinated polyamic acid. These reactive groups can react with epoxy resin to form a more dense and stable cross-linked network structure, thereby improving the corrosion resistance of the system and improving the mechanical properties; in addition, the polarized bonds generated by the nitrogen atoms in the pyridine ring increase the interaction between it and the epoxy resin, further improving the corrosion resistance of the system.

[0042] Polyurea has controllable soft and hard segments, and the polarity of the urea group is large, and hydrogen bonds can be formed. Therefore, compared with polyurethane, polyurea has better toughness and temperature resistance. The present invention uses polyurea to modify epoxy resin, which can significantly improve the brittleness of the system, enhance the mechanical properties, and further improve the temperature resistance of the system.

[0043] Nano-titanium has good corrosion resistance. The titanium in the nano-titanium alloy polymer containing epoxy groups is in the molecular chain structure of the polymer. Therefore, the nano-titanium alloy polymer containing epoxy groups not only has good corrosion resistance, but also has good compatibility with the main resin and can form a strong interface bonding force. In addition, the epoxy groups retained in the nano-titanium alloy polymer containing epoxy groups can cross-link with the amino, carboxyl and amide groups in component B to form a three-dimensional network structure, further improving the corrosion resistance of the system.

[0044] Fillers can be used in the main resin to improve its corrosion resistance and mechanical properties, but fillers are not easy to disperse evenly and have poor interface bonding with the main resin. The present invention uses an epoxy silane coupling agent to modify the filler, which can improve its dispersibility and the interface bonding problem with the main resin; at the same time, the epoxy group of the epoxy silane coupling agent can cross-link with the amino group, carboxyl group, and amide group of the B component in the main resin to form a three-dimensional network structure, thereby improving the overall strength and density of the coating and improving its anti-corrosion performance.

[0045] In summary, the present invention adopts a compound of low molecular weight polyamide and amino-terminated pyridine-containing fluorinated polyamic acid as component B; polyurea-modified epoxy resin, epoxy-containing nano-titanium alloy polymer and epoxy-modified filler are used as component A; after cross-linking and curing, components A and B form a dense three-dimensional network structure, which gives the coating excellent temperature resistance, corrosion resistance and mechanical properties.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] The present invention adopts a compound of low molecular weight polyamide and amino-terminated pyridine-containing fluorinated polyamic acid as component B, giving the coating good high and low temperature alternating resistance and corrosion resistance. At the same time, polyurea-modified epoxy resin, epoxy-containing nano-titanium alloy polymer and epoxy-modified filler are used as component A. The components A and B are mixed and coated on the outside of the steel strand body through a coating process. After curing, a stable and dense three-dimensional network structure is formed, and finally the coating is given excellent corrosion resistance and temperature resistance, and the high and low temperature alternating tensile shear strength retention rate is above 95%; the steel strand coated with the coating is suitable for flexible photovoltaic brackets. DETAILED DESCRIPTION

[0048] The present invention will be further described below in conjunction with specific embodiments, but is not limited to the contents in the specification. Unless otherwise specified, the "parts" described in the embodiments of the present invention are all parts by weight. Unless otherwise specified, the reagents used are all commercially available reagents in this area.

[0049] The epoxy resin solution is selected from NPES-901-60 produced by Nan Ya, that is, NPES-901 solution with a solid content of 60%. NPES-901 is a bisphenol A epoxy resin with an epoxy value of 0.21 eq / 100 g.

[0050] The nano titanium alloy polymer containing epoxy group is selected from XK-206 of Harbin Xinke Nanotechnology Development Co., Ltd., with a polymerization degree n of 12-15, and is a condensation product of bisphenol A cyclic resin and titanium hydride powder.

[0051] Preparation of amino-terminated pyridine-containing fluorinated polyamic acid

[0052] Preparation Example a1

[0053] (P1) 2,3-diamino-5-fluoropyridine was dissolved in DMAC, and BPDA was added into a reaction kettle in three batches according to a molar ratio of 2,3-diamino-5-fluoro to 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) of 1.1:1, and nitrogen was passed through the reaction kettle, and the reaction was stirred at 5° C. for 4 hours to obtain an amino-terminated pyridine-containing fluorinated polyamic acid solution;

[0054] (P2) After the reaction is completed, the amino-terminated pyridine-containing fluorinated polyamic acid solution is vacuum dried at 50° C. for 24 h to obtain the amino-terminated pyridine-containing fluorinated polyamic acid a1.

[0055] The number average molecular weight of the amino-terminated pyridine-containing fluorinated polyamic acid a1 was measured by GPC method and was found to be about 1,700.

[0056] Preparation Example a2

[0057] The rest is the same as Preparation Example a1, except that 2,6-diamino-3,5-difluoropyridine is used instead of 2,3-diamino-5-fluoropyridine in step (P1) to prepare amino-terminated pyridine-containing fluorinated polyamic acid a2. The number average molecular weight of amino-terminated pyridine-containing fluorinated polyamic acid a2 is about 1900 as measured by GPC.

[0058] Preparation Example a3

[0059] The rest is the same as Preparation Example a1, except that in step (P1), pyromellitic anhydride (PMDA) is used instead of BPDA, and the molar ratio of 2,3-diamino-5-fluoropyridine to BPDA is 1.3:1, to obtain amino-terminated pyridine-containing fluorinated polyamic acid a3. The number average molecular weight of amino-terminated pyridine-containing fluorinated polyamic acid a3 is about 1800 as measured by GPC.

[0060] Preparation of epoxy modified fillers

[0061] Preparation Example b1

[0062] (L1) Light calcium carbonate with a D50 of 25 μm was placed in a drying oven at 90° C. and dried for 24 h;

[0063] (L2) putting the dried light calcium carbonate into a high-speed mixer and stirring at 800 r / min for 4 h;

[0064] (L3) Spray 25 parts of an 8 wt % ethanol solution of 3-(2,3-epoxypropoxy)propyltriethoxysilane onto the surface of 100 parts of the filler obtained in step (L2), increase the stirring speed to 1300 r / min, and stop stirring after stirring for 60 min to obtain epoxy-modified filler b1.

[0065] Preparation Example b2

[0066] The rest is the same as Preparation Example b1, except that the filler is wollastonite with a D50 of 30 μm, and the silane coupling agent uses 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane instead of 3-(2,3-epoxypropyloxy)propyltriethoxysilane to obtain epoxy-modified filler b2.

[0067] Example 1

[0068] (I) Preparation of component A:

[0069] Raw material composition (parts by mass):

[0070]

[0071] Preparation steps:

[0072] S1: 4,4'-diaminodiphenyl ether (ODA) was dissolved in DMAC, and then toluene-2,4-diisocyanate (TDI) was added, and the temperature was raised to 80°C under nitrogen protection and stirred for reaction for 3 hours. After the reaction was completed, the product was vacuum dried at 60°C for 24 hours to obtain a polyurea prepolymer;

[0073] S2: Put the polyurea prepolymer obtained in step S1 into a reaction kettle, add epoxy resin NPES-901-60 under stirring, and react at 75° C. for 4 hours; cool to room temperature to obtain a polyurea-modified epoxy resin;

[0074] S3: adding epoxy modified filler b1, epoxy-containing nano titanium alloy polymer XK-206, and dispersant BYK-170 to polyurea modified epoxy resin, and ball milling in a planetary ball mill for 10 hours, and obtaining a mixed slurry after the ball milling is completed, namely component A;

[0075] (II) Preparation of component B: 203 low molecular weight polyamide and amino-terminated pyridine-containing fluorinated polyamic acid a1 were mixed and stirred in a mass ratio of 1:1 to obtain a mixed slurry, namely component B;

[0076] (III) Coating: Component A obtained in step (I) and component B obtained in step (II) are mixed in a mass ratio of 1:0.4, and then applied to the steel strand body by a coating device with a spring control arm on a roller brush. During coating, the steel strand body passes through the device, driving the roller brush to rotate along the steel wire, and the coating thickness is controlled at 2±0.2 mm; the temperature of the tail section of the coating device is 75°C.

[0077] (IV) Curing: The steel strand coated with the film is cured at 85°C for 48 hours.

[0078] Example 2

[0079] The rest is the same as Example 1, except that component B is a compound of 203 low molecular weight polyamide and amino-terminated pyridine-containing fluorinated polyamic acid a2 in a mass ratio of 1:2.

[0080] Example 3

[0081] The rest is the same as Example 1, except that component B is a compound of 651 low molecular weight polyamide and amino-terminated pyridine-containing fluorinated polyamic acid a3 in a mass ratio of 1:3.

[0082] Example 4

[0083] The rest is the same as Example 1, except that the raw material composition of component A is different.

[0084] The raw material composition of component A is (parts by mass):

[0085]

[0086] Example 5

[0087] The rest is the same as Example 4, except that in step (III), the mass ratio of component A to component B is 1:0.6.

[0088] Comparative Example 1

[0089] The rest is the same as Example 1, except that component B is 203 low molecular weight polyamide, and amino-terminated pyridine-containing fluorinated polyamic acid is not compounded.

[0090] Test results and analysis

[0091] The steel strand coatings prepared in the above examples and comparative examples were tested for temperature resistance and corrosion resistance, and the data are shown in Table 1.

[0092] High and low temperature alternating performance: refer to standard JG / T 370-2012 to carry out high and low temperature alternation at -25±2℃ and 35±2℃. After the alternation, balance to room temperature, test the tensile shear strength, and calculate the tensile shear strength retention rate.

[0093] Corrosion resistance: Soak the samples in 10% H2SO4, 10% HCl, 10% NaOH, and 10% NaCl for 720 hours respectively, and observe the blistering, rusting, and detachment of the samples with the naked eye.

[0094] Salt spray resistance: Test according to GB / T 1771-2007. Take out the sample after 3000 hours and observe the blistering, rusting, detachment and other phenomena with naked eyes.

[0095] Table 1 Performance test

[0096]

[0097] It can be seen from Table 1 that the modified epoxy resin composition described in the present invention is coated on the outside of the steel strand body, and the formed coating has not only good corrosion resistance, but also excellent temperature resistance, and the high and low temperature alternating tensile shear strength retention rate is above 95%; therefore, the steel strand coated with the coating meets the temperature resistance and corrosion resistance requirements of the flexible photovoltaic bracket.

[0098] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.

Claims

1. A modified epoxy resin composition suitable for use as an outer coating for a flexible photovoltaic support steel strand, characterized in that: The composition comprises a component A and a component B, wherein the component A comprises the following raw materials in parts by weight: 100 parts of 4,4'-diaminodiphenyl ether, 90-110 parts of toluene-2,4-diisocyanate, 750-900 parts of epoxy resin solution, 40-50 parts of nano titanium alloy polymer containing epoxy group, 30-50 parts of epoxy modified filler, and 2-5 parts of dispersant; wherein 4,4'-diaminodiphenyl ether, toluene-2,4-diisocyanate, and epoxy resin solution are used as raw materials to prepare polyurea modified epoxy resin; the component B is low molecular weight polyamide and amino-terminated pyridine-containing fluorinated polyamic acid in a mass ratio of 1: (1-3); the number average molecular weight of the amino-terminated pyridine-containing fluorinated polyamic acid is 1000-3000; the amino-terminated pyridine-containing fluorinated polyamic acid is prepared by reacting raw materials including a fluorinated diamine containing pyridine and a dibasic acid anhydride, and the molar ratio of the fluorinated diamine containing pyridine to the dibasic acid anhydride is (1.1-1.3):1; The pyridine-containing fluorinated diamine is selected from at least one of 2,3-diamino-5-fluoropyridine, 2,6-diamino-3-fluoropyridine, and 2,6-diamino-3,5-difluoropyridine; the dibasic acid anhydride is selected from at least one of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) and pyromellitic dianhydride (PMDA).

2. The modified epoxy resin composition according to claim 1, characterized in that The B component is a compound of low molecular weight polyamide and amino-terminated pyridine-containing fluorinated polyamic acid in a mass ratio of 1: (2-3).

3. The modified epoxy resin composition according to claim 1, characterized in that The molecular weight of the low molecular weight polyamide in the B component is 600-2000.

4. The modified epoxy resin composition according to claim 1, characterized in that The epoxy resin in the epoxy resin solution is at least one of bisphenol A epoxy resins with an epoxy value of 0.1 to 0.3 eq / 100g, and the solid content of the epoxy resin solution is 50% to 70%.

5. The modified epoxy resin composition according to claim 1, characterized in that The epoxy-containing nano titanium alloy polymer in the A component is a polycondensate of bisphenol A epoxy resin with an epoxy value of 0.6-1.0 eq / 100g and titanium hydride powder, and the polymerization degree n is 5-20.

6. A flexible photovoltaic support steel strand, comprising a steel strand body and a coating wrapped around the steel strand body, characterized in that: The coating is formed by coating the epoxy resin composition of any one of claims 1 to 5 on the steel strand body and then curing it by heating, wherein the coating is performed by mixing component A and component B in a mass ratio of 1:0.4 to 0.

6.

7. The method for preparing the flexible photovoltaic support steel strand according to claim 6, characterized in that: The following steps are involved: (I) Preparation of component A: S1: dissolving 4,4'-diaminodiphenyl ether in an organic solvent, then adding toluene-2,4-diisocyanate, heating under nitrogen protection to react, and after the reaction is completed, the product is vacuum dried to obtain a polyurea prepolymer; S2: putting the polyurea prepolymer obtained in step S1 into a reaction kettle, adding the epoxy resin solution under stirring, heating to react; cooling to room temperature to form a polyurea-modified epoxy resin; S3: adding epoxy-modified filler, epoxy-containing nano-titanium alloy polymer and dispersant to polyurea-modified epoxy resin, and ball milling in a ball mill for 6-12 hours. After the ball milling is completed, a mixed slurry is obtained, which is component A; (II) Preparation of component B: low molecular weight polyamide and amino-terminated pyridine-containing fluorinated polyamic acid are mixed and stirred according to a mass ratio to obtain a mixed slurry, namely component B; (III) Coating: Component A prepared in step (I) and component B prepared in step (II) are mixed in a mass ratio of 1:0.4-0.6, and then applied to the steel strand. The coating thickness is controlled at 1.5-2.5 mm. The temperature of the end section of the coating device is 70-85°C. (IV) Curing: The steel strand coated with the film is heated and cured.

Citation Information

Patent Citations

  • Retard-bonded prestressed steel bar and preparation method thereof

    CN111424884A

  • Polyurea modified epoxy resin anticorrosive paint and preparation method thereof

    CN117343612A

  • Polyurethane modified epoxy resin composition and annularly arranged steel strand suitable for wind power mixing tower

    CN118006211A

  • Epoxy resin composition and preparation method thereof

    CN118256063A